The Influence of Educational Staff Services and Teacher Competence on Student Satisfaction Through Student Loyalty With Competitor Intensity as a Moderating Variable - Lathifah, Najmi Diyana; Wahyudin, Agus; Oktarina, Nina (Journal of Vocational and Career Education, 2025)
The growing competition among private high schools has made student satisfaction and loyalty crucial for educational sustainability. This study aims to analyze the influence of educational staff services and teacher competence on student satisfaction and loyalty in private high schools in Padang Timur District, with competitor intensity as a moderating variable. A quantitative survey was conducted with 280 respondents using proportional stratified random sampling, and data were analyzed through path analysis, Sobel test, and Moderated Regression Analysis (MRA). The findings indicate that both educational staff services and teacher competence significantly affect student satisfaction and loyalty, with satisfaction acting as a partial mediator, while competitor intensity weakens the satisfaction–loyalty relationship. These results highlight the need for continuous improvement in administrative services, teacher competence, and clear differentiation strategies to sustain competitiveness in education.